Comparison Between Two Different Doses of Oral Pregabalin Given Pre-Emptively on Duration of Spinal Anesthesia and Postoperative Pain in Lower Limb Surgeries - Obaid, Abubakar; Khan, Ahad Ali; Khalid, Marriam; Butt, Mahnoor Rafique; Mir, Ahmed Jahangir; Javed, Hafiz Muhammad (Biological and Clinical Sciences Research Journal, 2025)
Optimal management of postoperative pain following lower limb surgeries remains a clinical challenge in resource-limited settings. Pregabalin, a gabapentinoid, has emerged as an effective adjunct for enhancing spinal anesthesia and reducing opioid requirements. This study aimed to compare the effects of 75 mg versus 150 mg of oral pregabalin administered preemptively on the duration of spinal anesthesia and postoperative pain control. Methods: This prospective comparative study was conducted at Aziz Bhatti Shaheed Hospital, Gujrat, from November 2022 to September 2023. Ninety adult patients scheduled for elective lower limb surgery under spinal anesthesia were randomized into two groups: Group A received 75 mg and Group B received 150 mg of oral pregabalin one hour before surgery. Duration of sensory and motor block, postoperative Visual Analogue Scale (VAS) pain scores, time to first rescue analgesia, and total 24-hour tramadol consumption were recorded. Results: The 150 mg pregabalin group demonstrated a significantly longer duration of sensory block (196.2 ± 19.4 min vs. 172.5 ± 15.8 min; p<0.001) and motor block (187.6 ± 18.9 min vs. 162.4 ± 14.7 min; p<0.001) than the 75 mg group. Postoperative VAS scores were consistently lower at all intervals in the 150 mg group (p<0.05). Time to first rescue analgesia was significantly delayed (224.8 ± 30.2 min vs. 174.3 ± 25.6 min; p<0.001), and total 24-hour tramadol requirement was significantly reduced (84.5 ± 13.7 mg vs. 107.8 ± 15.3 mg; p<0.001) in the higher dose group. Conclusion: Preemptive administration of 150 mg oral pregabalin significantly prolongs spinal block duration, reduces postoperative pain scores, and minimizes opioid consumption compared to 75 mg. It presents a viable strategy for enhanced perioperative analgesia in lower limb surgeries within the Pakistani population.